Glycyrrhiza uralensis Flavonoids Present in Anti‐Asthma Formula, ASHMITM, Inhibit Memory Th2 Responses in Vitro and in Vivo. (19th November 2012) - Yang, Nan; Patil, Sangita; Zhuge, Jian; Wen, Ming‐Chun; Bolleddula, Jayaprakasam; Doddaga, Srinivasulu; Goldfarb, Joseph; Sampson, Hugh A.; Li, Xiu‐Min
Abstract : Allergic asthma is associated with Th2‐mediated inflammation. Several flavonoids were isolated from Glycyrrhiza uralensis, one of the herbs in the anti‐asthma herbal medicine intervention. The aim of this investigation was to determine whether Glycyrrhiza uralensis flavonoids have inhibitory effects on memory Th2 responses in vitro and antigen‐induced Th2 inflammation in vivo . The effects of three Glycyrrhiza uralensis flavonoids on effector memory Th2 cells, D10.G4.1 (D10 cells), were determined by measuring Th2 cytokine production. Isoliquiritigenin, 7, 4′‐dihydroxyflavone (7, 4′‐DHF) and liquiritigenin significantly suppressed IL‐4 and IL‐5 production in a dose‐dependent manner, 7, 4′‐DHF being most potent. It was also evaluated for effects on D10 cell proliferation, GATA‐3 expression and IL‐4 mRNA expression, which were suppressed, with no loss of cell viability. Chronic treatment with 7, 4′‐DHF in a murine model of allergic asthma not only significantly reduced eosinophilic pulmonary inflammation, serum IgE levels, IL‐4 and IL‐13 levels, but also increased IFN‐γ production in lung cell cultures in response to antigen stimulation. Copyright © 2012 John Wiley & Sons, Ltd.